Trans-Disciplinary Responses to Climate Change: Lessons from Rice-Based Systems in Asia - Hellin, Jonathan; Balié, Jean; Fisher, Eleanor; Kohli, Ajay; Connor, Melanie; Yadav, Sudhir; Kumar, Virender; Krupnik, Timothy J.; Sander, Björn Ole; Cobb, Joshua N.; Nelson, Katherine; Setiyono, Tri; et al. (MDPI, 2020)
"Climate change will continue to have a largely detrimental impact on the agricultural sector worldwide because of predicted rising temperatures, variable rainfall, and an increase in extreme weather events. Reduced crop yields will lead to higher food prices and increased hardship for low income populations, especially in urban areas. Action on climate change is one of the Sustainable Development Goals (SDG 13) and is linked to the Paris Climate Agreement. The research challenge posed by climate change is so complex that a trans-disciplinary response is required, one that brings together researchers, practitioners, and policy-makers in networks where the lines between “research” and “development” become deliberately blurred. Fostering such networks will require researchers, throughout the world, not only to work across disciplines but also to pursue new South–North and South–South partnerships incorporating policy-makers and practitioners. We use our diverse research experiences to describe the emergence of such networks, such as the Direct Seeded Rice Consortium (DSRC) in South and Southeast Asia, and to identify lessons on how to facilitate and strengthen the development of trans-disciplinary responses to climate change."